COGNITIVE LINGUISTICS FOR TRANSLATION STUDIES AND TRANSLATOR TRAINING - Gheorghiță, Elena (CEP USM, 2014)
The focal topic of the article is the discussion of the links between translation studies and ognitive linguistics and of the applicability of methodology developed for cognitive linguistics in translation studies and translator training, spe- cifically of conceptual analysis of linguistic meaning in general and in translation studies and translator training in particular. Special attention will be paid to the semantics of lingual tworks, a method developed by S.Zhabotynska, which may prove helpful both in theoretical and ractical studies of terminology

Articolul de faţă are ca subiect legăturile dintre lingvistica cognitivă şi studiul teoretic şi practic al traducerii, în vizor fiind luata şi aplicabilitatea metodelor elaborate pentru lingvistica cognitivă în traductologie şi didactica traducerii. Atenţie specială se va acorda metodei numite ,,semantica reţelelor linguale”, elaborate de cercetătoarea ucraineană S.Zhabotynska. Metoda respectivă poate fi utilă atât pentru cercetări traductologice, cât şi pentru instruirea viitorilor traducători practicieni: procesul de studiere a terminologiei de specialitate ar putea fi mai bine organizat.
INSTRUMENTARUL LINGVISTICII COGNITIVE ÎN SERVICIUL TRADUCTOLOGIEI Ş I INSTRUIRII TRADUC Ă TORILOR
Keywords: cognitive lingvistics; conceptul analysis; translation; lingvistică cognitivă; instruirea traducătorilor